The picture frames are as an object of cultural heritage and a detail of art interior - Luiza Albastova (Periodica Journal, 2022)
The history of the art frame is described in detail in the works of European and American researchers. A big interest in frames arose a quarter of a century ago. There was an exhibition of American frames of the 18th-19th c. in Chicago in 1983. In the early 1990s in the Metropolitan Museum of Art in New York and in the Bagatel Palace in Paris were the exhibitions dedicated to Italian and French carved gilded frames.
Keywords: Art Frames; Contemporary Art; Cultural Heritage; Interior